Simulation of temporary plugging agent transport and optimization of fracturing parameters based on fiber optic monitoring data - Jingchen, Zhang; Xiaodong, Guo; Mingxing, Wang; Jie, Li; Shanzhi, Shi; Guangcong, Ren (Frontiers in Chemical Engineering, 2024)
Temporary plugging and fracturing is an important technology for the efficient development of unconventional reservoirs. Due to the diverse physical properties of unconventional reservoirs and the complex stress environment, the evaluation of temporary plugging effect needs to consider the working conditions in the wells, and it also needs to focus on the transport and placement of temporary plugging agent in the near-well fracture region, so it is impossible to predict the effect of temporary plugging and fracturing effectively. In this paper, a numerical simulation study is carried out to investigate the transport and placement of temporary plugging agent in the near-well area, and a finite element model of “wellbore-near-well fracture” is established based on computational fluid dynamics, and numerical simulation and verification of temporary plugging and fracturing are carried out based on the fiber-optic monitoring data of temporary plugging and fracturing in Well A, as well as the optimization of some construction parameters. The results show that: as the volume concentration of temporary plugging agent increases, the temporary plugging effect is weakened and then strengthened, and the temporary plugging agent will enter into the heel cluster in advance when the concentration is small; at the initial stage, the increase in the quality of temporary plugging agent will cause some clusters to form incomplete plugging, but the quality of the plugging agent will not be changed after the quality is greater than 360kg; the temporary plugging effect is mainly reflected in the heel cluster, and the toe cluster is not obvious. This paper forms a set of temporary plugging and fracturing simulation methods based on the actual fiber-optic monitoring data in the field, which provides a reference for the optimization design of the type, particle size and dosage of temporary plugging agent during the temporary plugging construction process.